The expanded bridge program in U.P. Visayas - Catedrilla, Liah C.; Galorport, Sharon Rose C.; Quintilla, Mae L. (Danyag :the UPV journal of humanities and social sciences, 2006)
"The paper describes the implementation of the Expanded Bridge Program )EBP) in 2004 and compares it with the implementation of the Summer Bridge Program (SBP) in 2003 in the Miagao and Iloilo City campuses of U.P. in the Visayas. The participants' performance in both the EBP 2004 and SBP 2003 were compared. In terms of participants' performance in Math 11 and Communication 1 and budget requirements, the implementation of EBP 2004 is more cost effective than that of SBP 2003."